2018
DOI: 10.1155/2018/6508709
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Effects on Inflammation and Platelet Activation Markers in Hypercholesterolemia

Abstract: Background Beside the lipid-lowering effect, statins slow the progression of atherosclerosis by exerting anti-inflammatory and platelet inhibiting effects. We investigated whether platelet inhibition by simvastatin correlates with the statin effects on lipid lowering, inflammation, oxidative stress, and endothelial and platelet activation. MethodsIn hypercholesterolemic patients allocated to diet (n=20) or a 2-month treatment with diet plus 40 mg simvastatin (n=25), we evaluated platelet aggregating responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 45 publications
(49 reference statements)
0
57
0
1
Order By: Relevance
“…Presumably, one of the causes may have been the statin therapy, as 96% of our patients received statins. There are reports of reductions in circulating IL-6 concentrations in patients taking statins [28,29]. They decrease the production and release of IL-6 in the endothelium and leukocytes [28,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, one of the causes may have been the statin therapy, as 96% of our patients received statins. There are reports of reductions in circulating IL-6 concentrations in patients taking statins [28,29]. They decrease the production and release of IL-6 in the endothelium and leukocytes [28,30].…”
Section: Discussionmentioning
confidence: 99%
“…Different types of statins vary in their potency of IL-6 release inhibition and the type of cells they affect [31,32]. Statins, apart from LDL-cholesterol lowering, exert pleiotropic effects on endothelial function, vascular inflammation, immunomodulation, and thrombogenesis, and therefore they prevent cardiovascular events, ameliorate the prognosis of patients affected by acute MI, as well as reduce the risk of restenosis after angioplasty [29]. Statins may have an anti-inflammatory effect on hsCRP level [33].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets from patients with hypercholesterolemia show hyperaggregability, increased fibrinogen binding and surface expression of CD62P, increased production of TXA 2 and superoxide anion, whereas plasma derived from the same patients contains increased concentrations of platelet activation markers, such as soluble sCD-40L, PF-4, sP-selectin, and β-thromboglobulin [182][183][184]. Many of these impaired platelet parameters of platelet aggregation and activation are corrected by lipid-lowering treatments.…”
Section: Role Of Dyslipidemia In the Impaired Platelet Reactivitymentioning
confidence: 99%
“…In vitro and in vivo studies show that statins, inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase and the most relevant drugs used to lower serum cholesterol levels, due to their pleiotropic effects decrease subclinical inflammation, oxidative stress, endothelial dysfunction, platelet aggregation, and activation [185][186][187][188][189], improving platelet sensitivity to NO [178], and aspirin [184], but not to GLP-1 [178]. The causes of the enhanced platelet hyperaggregability and the defective GLP-1 actions in dyslipidemia can be multifactorial, although the strong correlation with LDL underlines the role of cholesterol as a major determinant of platelet hyperreactivity with a putative role also in the impaired response to GLP-1.…”
Section: Role Of Dyslipidemia In the Impaired Platelet Reactivitymentioning
confidence: 99%
“…In this context administration of simvastatin at a dose of 20 mg/daily for 6 weeks to hypercholesterolemic patients resulted in significantly decreased concentrations of cholesterol in the plasma membranes of isolated blood neutrophils (178). These anti-platelet activities of statins have also been described in the clinical setting, albeit in newly-diagnosed patients with primary hypercholesterolemia treated with simvastatin (179). In this study, Barale et al observed that aside from improved lipid profiles, administration of simvastatin was associated with significant reduction in ADP-and collagen-activated platelet aggregation ex vivo, as well as reductions in systemic biomarkers of platelet activation, including sCD62P, sCD40L, plateletderived growth factor BB and RANTES.…”
Section: Statinsmentioning
confidence: 94%